Ayurvedic Management of Recurrent Pregnancy Loss (International Journal of Ayurveda and Pharma Research, 2025)
Recurrent pregnancy loss is relatively common event occurring in 15-25% of pregnancies and increasing in prevalence with maternal age which in turn leads to infertility. The prognosis for couples with recurrent pregnancy loss is generally good, although the likelihood of a successful pregnancy depends on maternal age and the number of previous losses. Recurrent pregnancy loss can be caused by chromosomal errors, anatomical uterine defects, autoimmune disorders and endometrial dysfunction. This is a case report of a 25 year old female with complaints of inability to conceive a viable fetus even after 1 and ½ years of unprotected sexual intercourse. She has regular menstrual cycles and has been conceived twice but was met with spontaneous abortion in both instances. As per Ayurveda, it could be considered Garbhasravi vandhya since both abortions occurred in the first trimester. Treatment plan included internal medications as well as Sodhana procedures for future healthy uneventful pregnancy. The integrative approach of Ayurveda offers promising solutions for addressing RPL by focusing on correcting systemic imbalances, improving reproductive health, and enhancing overall immunity. The case study discussed highlights the therapeutic potential of Ayurvedic interventions.